HIV and Sexual Dysfunction in Men - De Vincentis, Sara (J Clin Med, 2021)
Sexual issues tend to go unaddressed in human immunodeficiency virus (HIV) management, although overt sexual dysfunctions are more prevalent in people living with HIV than uninfected people. Erectile dysfunction is the most frequent sexual problem, with a prevalence of 30–50% even in men <40 years of age, but other issues such as loss of libido and ejaculatory disorders should not be overlooked. Peculiar factors related to HIV infection (e.g., fear of virus transmission, changes in body image, HIV-related comorbidities, HIV distress and stigma), alongside classical factors non-related to HIV, should be considered when approaching sexual problems in HIV patients. For this reason, the diagnostic and therapeutic workout of sexual dysfunction in the context of HIV requires a multidisciplinary approach, involving specialists in both infectious diseases and sexual medicine. This narrative review presents an overview of current knowledge on sexual dysfunction in HIV men, deepening the factors driving and taking part in these issues, providing advice for the clinical approach, and underlining the importance of caring for sexual health to improve the quality of life of HIV patients.